Dimensions of Patient Experience and Overall Satisfaction in Emergency Departments. (September 2017) - Tanniru, Mohan; Khuntia, Jiban
Objective: To determine the correlation between individual patient experience dimensions and overall patient satisfaction using text-based analysis of subjective comments of patients treated in emergency departments. Methods: Open-ended comments from 331 patients who visited the emergency departments of 4 hospitals were used for coding different dimensions of patient experience. Regression coefficients were calculated to assess the relationships between dimensions of patient experiences with overall satisfaction. Results: Positive and negative experience of nursing, communications, and infrastructure influence the overall satisfaction. Positive experience attributes of overall care quality influence overall satisfaction, whereas negative experience of the same does not have any influence. Further, experiences of interactions with doctors and scheduling do not have any effect on overall satisfaction in emergency departments. Conclusions: Emergency departments may get higher overall patient evaluations by focusing on positive aspects of care, nursing, communication, and infrastructure attributes. Doctors and scheduling (emergency) may be considered as expected quality attributes and so not surprising that they did not play a role in overall satisfaction.